Anticorrosion potential of a bioemulsifier produced by Psychrobacillus antarcticus Val9 isolated from Antarctic soil - de Castilho, Lívia Vieira Araujo; Barreto, Aline Loureiro; Santaren, Karen Caroline Ferreira; Rosenblatt, Mariana Barbalho Farias; Taveira, Igor; Cypriano, Jefferson; Abreu, Fernanda; de Godoy, Mateus Gomes; Jurelevicius, Diogo de Azevedo; Seldin, Lucy (Frontiers in Microbiology, 2026)
IntroductionMicrobiologically influenced corrosion (MIC) poses a persistent challenge in industrial systems, particularly in oilfield infrastructure, where biofilm-forming microorganisms accelerate metal degradation. This study evaluated the anticorrosive, antibiofilm, and biocidal properties of two bioproducts—a bioemulsifier from Psychrobacillus antarcticus Val9 and a surfactin from Bacillus velezensis H2O-1— simulating water injection header conditions.MethodsThe bioproducts were produced and characterized through emulsification indices, surface tension, and oil displacement assays. Their protective effects against biocorrosion were assessed via carbon steel mass loss, scanning electron microscopy, epifluorescence microscopy, surface roughness analysis, ATP quantification, and molecular profiling of microbial communities.Results and DiscussionThe compounds demonstrated desirable physicochemical properties and maintained stability under the tested conditions. All the treatments significantly reduced the carbon steel mass loss over 96 h, with protection rates ranging from 58.2% ± 11.3 to 94.6% ± 2.0. Microscopic analyses revealed diminished biofilm roughness and disrupted extracellular matrix cohesion, indicating impaired biofilm maturation. ATP assays and qPCR data revealed selective microbial suppression without triggering metabolic rebound, suggesting the destabilization of biofilm homeostasis. Furthermore, 16S rRNA gene sequencing and absolute quantification revealed a shift in the microbial community structure, with a reduced abundance of corrosion-associated taxa and enrichment of fewer metal-aggressive genera.ConclusionThese findings highlight the dual action of the tested bioproducts: direct surface protection and strategic microbial community modulation. This integrated approach offers a sustainable alternative to conventional chemical biocides, with potential applications in offshore pipelines and industrial water systems.